COVID‐19 vaccination in children and adolescents aged 5 years and older undergoing treatment for cancer and non‐malignant haematological conditions: Australian and New Zealand Children's Haematology/Oncology Group consensus statement. Issue 6 (10th March 2022) - Furlong, Eliska; Kotecha, Rishi S; Conyers, Rachel; O'Brien, Tracey A; Hansford, Jordan R; Super, Leanne; Downie, Peter; Eisenstat, David D; Haeusler, Gabrielle; McMullan, Brendan; Phillips, Marianne B; Padhye, Bhavna; et al.
Abstract: Introduction: The Australian Technical Advisory Group on Immunisation and New Zealand Ministry of Health recommend all children aged ≥ 5 years receive either of the two mRNA COVID‐19 vaccines: Comirnaty (Pfizer), available in both Australia and New Zealand, or Spikevax (Moderna), available in Australia only. Both vaccines are efficacious and safe in the general population, including children. Children and adolescents undergoing treatment for cancer and immunosuppressive therapy for non‐malignant haematological conditions are particularly vulnerable, with an increased risk of severe or fatal COVID‐19. There remains a paucity of data regarding the immune response to COVID‐19 vaccines in immunosuppressed paediatric populations, with data suggestive of reduced immunogenicity of the vaccine in immunocompromised adults. Recommendations: Considering the safety profile of mRNA COVID‐19 vaccines and the increased risk of severe COVID‐19 in immunocompromised children and adolescents, COVID‐19 vaccination is strongly recommended for this at‐risk population. We provide a number of recommendations regarding COVID‐19 vaccination in this population where immunosuppressive, chemotherapeutic and/or targeted biological agents are used. These include the timing of vaccination in patients undergoing active treatment, management of specific situations where vaccination is contraindicated or recommended under special precautions, and additional vaccination recommendations for severely immunocompromised patients. Finally, we stress the importance of upcoming clinical trials to identify the safest and most efficacious vaccination regimen for this population. Changes in management as a result of this statement: This consensus statement provides recommendations for COVID‐19 vaccination in children and adolescents aged ≥ 5 years with cancer and immunocompromising non‐malignant haematological conditions, based on evidence, national and international guidelines and expert opinion. Endorsed by: The Australian and New Zealand Children's Haematology/Oncology Group.